Basic principles of construction and organization of the enterprise corporate innovative system - N. V. Alekseeva; M. B. Bobrova; A. F. Sazonov (Вестник университета)
Four basic principles, necessary for the enterprises for successful development of space of a corporate innovative system within the fourth industrial revolution «Industry-4», have been highlighted. These include globality, openness, partnership of businessmen and network organization. It has been proved, that the hi-tech enterprises, working in Russia, already today need to create and actively develop space: standard, digital, technological, physical, ideological, organizational, in which various innovative initiatives and projects will be able effectively to work.